Changing stress levels through gaining information on stress - S.N. Madu; E.S. De Jong (AOSIS, 2002)
Objective: The aim of this research was to find out the effect of the Information Phase of a Stress Management Program (SMP) on the perceptions of participants about their stress levels. Method: A total sample of 100 workers (nursing staff, private business men and women, laboratory assistants, the protective services [foreman and security staff], as well as people in human resources departments) took part in this study. All the participants were from the Northern and Gauteng Provinces in South Africa. The Combined Hassles and Uplifts Scale (Folkman & Lazarus, 1989) was used as an instrument to measure the perceived stress level of participants in a SMP. Result: A significant reduction in stress levels was achieved among those who received the Information Phase of the SMP only, as well as those who received the whole stress management techniques. There was no significant difference between the amount of reduction in perceived stress-levels achieved among those that received the Information Phase of the SMP only, compared to that of those who received the whole techniques. Conclusion: The authors conclude that where the resources are limited, only the information phase of a SMP may be given to desiring clients. That should help to save time and money spent on participating in SMPs. This should however not discourage the use of the whole SPM, where affordable. Keywords: Stress Management Programs, Information Phase, Perception, Stress Level.